The role of R&D and universities in patenting and scientific publications, and economic growth: A study of Malaysia / Than Lee Lee - Than, Lee Lee (2022)
Using patents, industrial designs, and scientific publications, this study examines the R&D performance of Malaysia over the period from 1996 to 2017. In doing so, the thesis also examines the state of research and patenting participation of Malaysian researchers, universities, and firms. Although not all patents eventually attract commercial value, given the complexities associated with R&D spillover, it is still widely used as an innovation output to support economic growth. In this regard, this thesis uses patent-to- GDP ratio alongside Catch-up Index estimate R&D expenditure and R&D performance gaps. The use of GERD-to-GDP is a weak indicator of innovative progress among particularly developing countries because a significant share of it do not go to supporting economic growth. Hence, studying this gap will allow us to understand the extent of commercialization that takes place from R&D investment in Malaysia. Using a variety of sources of national and international data on patent and growth, and the Error Correction Model, and Autoregressive Distributed Lag (ECM-ARDL) approach, we construct an analytical model using the theoretical concepts of Romer’s endogenous growth on innovation and Griliches’s knowledge production framework to advance this study, though we eventually criticize the Romer and Grichiches’ models for not including innovation inputs (e.g., R&D investment) and output (e.g., patents, especially domestic patents). The model consists of patent, industrial design, GERD, fixed capital formation, employed scientific human capital and GDP growth to measure the process of innovation, and their association with economic development. The results show that both patents and industrial designs are significantly correlated with economic growth in the overall sample but is negatively correlated in the short run in the Malaysian data, though the long run relationship between Malaysian patents and the trade structure is positively correlated. Also, patent-to-GDP and industrial design-to-GDP ratios affect patenting activities in Malaysia. Consequently, while it is fine to continue the focus on scientific publications, the knowledge created should also be used to file patents and industrial designs. The science, technology and innovation (STI) infrastructure in Malaysia requires a revision to raise the focus on patenting and commercialization. Malaysia remains a strong candidate among the Asian-8 economies to make the transition to high-tech developed country status if the increasing trend of R&D investment is translated into patenting. That the potential exists cannot be dismissed as the country has witnessed a sharp rise in scientific publications since 2005. In addition, there is a need to improve university industry linkages to overcome such a shortcoming. In doing so, efforts must be taken to reinvigorate the science and number parks in Malaysia through requiring researchers granted research incentives and grants to undertake prototyping and new product development.